Is Arm-span an accurate measure of stature? A cross sectional study in North Indian population - Rai, Pinki; Das, Ashima; Kumar, Surendra; Girdhar, Ritika; Kumar, Paras; Saini, Nishtha (Asian Journal of Medical Sciences, 2021)
Background: The estimation of inter-relationship between various body parameters and stature has been an important tool in anthropometric measurements. It is found to be of great importance in such cases where direct measurement of stature is not possible. A wide variety of parameters are used for estimation of stature including arm spam, hand length, foot length, demi span, knee height, sitting position etc. In this study arm span is used for stature estimation. Aims and Objective: To find the accuracy of arm-span in predicting standing height of both males and females in studied population. Materials and Methods: The study involved 600 participants (300 males and 300 females). The data for study collected from Rajasthan by means of community visits. The standing height and arm-span were measured for each individual and analyzed. Correlation coefficient and regression equation was generated. Results: A positive correlation was found to exist between the arm-span and stature. The correlation coefficient r was found to be 0.9. In the studied population, the arm span was found to be a strong predictor of Stature. Conclusion: It can be concluded that arm-span can be used in estimation of the height of both males and females. Arm span is reliable tool for obtaining the approximate stature of an individual. It can be used for the purpose of medico-legal cases too.